2022
DOI: 10.1038/s41416-022-01727-4
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids as anticancer drugs: current status of preclinical research

Abstract: Drugs that target the endocannabinoid system are of interest as pharmacological options to combat cancer and to improve the life quality of cancer patients. From this perspective, cannabinoid compounds have been successfully tested as a systemic therapeutic option in a number of preclinical models over the past decades. As a result of these efforts, a large body of data suggests that the anticancer effects of cannabinoids are exerted at multiple levels of tumour progression via different signal transduction me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 158 publications
1
58
0
4
Order By: Relevance
“…Cannabinoid agonists modulate various cancer-related pathways that can lead to the blockade of the cell cycle, inhibition of the cell proliferation and cell death [ 23 ]. Cannabinoid ligands (including CBD) possess the anti-invasiveness and anti-metastatic actions [ 24 , 25 , 26 ]. Cannabinoids also exert the anti-angiogenesis effects by blocking the activation of the vascular endothelial growth factor pathway [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cannabinoid agonists modulate various cancer-related pathways that can lead to the blockade of the cell cycle, inhibition of the cell proliferation and cell death [ 23 ]. Cannabinoid ligands (including CBD) possess the anti-invasiveness and anti-metastatic actions [ 24 , 25 , 26 ]. Cannabinoids also exert the anti-angiogenesis effects by blocking the activation of the vascular endothelial growth factor pathway [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of different cannabinoids have shown antitumour effects in many preclinical studies when applied individually (for review see [1,2]). In the present study, the combination of THC and CBD showed a synergistic inhibitory effect on the viability of human glioblastoma cells at 5 µM each, and can therefore be considered as a promising add-on therapy for glioblastoma, which is in agreement with the studies of other authors [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Soon after, a growth inhibitory effect on glioma xenografts was confirmed for the selective cannabinoid receptor CB 2 agonist JWH-133 [5]. In the meantime, cannabinoid-mediated anticancer effects have also been demonstrated in a variety of other tumour entities, whereby the effects shown here range from the initially demonstrated inhibition of proliferation and induction of tumour cell apoptosis to proautophagic, anti-angiogenic, anti-invasive and antimetastatic effects (for review see [1,2]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have already mentioned, cannabinoid agonists, in addition to their analgesic, antianorexic and antiemetic effects, have shown their utility in different in vitro and in vivo models of cancer, including lung cancer [ 29 ]. The combined use of THC and powerful CBD has shown the potential to enhance these effects, also reducing the harmful effects of THC at the level of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%